Menstimulasi Kepuasan Pelanggan dalam Ekonomi Kreatif: Penilaian Strategis Harga dan Kualitas Produk pada Toko Citra Oleh-Oleh Warisan Budaya Lampung - Chantika Putri; Susi Indriyani; Evi Meidasari (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2026)
This quantitative study aims to analyze the influence of product quality and price on customer satisfaction at Citra Lampung Souvenir Store. The study involved 306 respondents selected through purposive sampling based on the Krejcie table. Data were analyzed using multiple linear regression with SPSS version 26. The results indicate that product quality has a positive and significant effect on customer satisfaction (sig. = 0.026; t = 2.242), while price also has a positive and significant effect (sig. = 0.000; t = 6.669) and is the most dominant variable. The coefficient of determination (R²) of 0.255 shows that product quality and price explain 25.5% of the variation in customer satisfaction, while the remaining 74.5% is influenced by other factors outside the research model. These findings confirm that consistent product quality and competitive pricing play important roles in enhancing customer satisfaction in regional souvenir businesses.